Opinion of Nurse Educators and Student Nurses on the Development of Direct Entry Graduate Program in Midwifery - Abraham, A; Tamang, L; Chhugani, M (International journal of nursing education, 2013)
To determine the opinion of nurse educators and student nurses and develop a syllabus for the direct entry graduate program in midwifery and further seek its acceptability. A descriptive survey approach was utilized for the study. The study was conducted in 14 schools and colleges of Nursing in Delhi. Total enumeration technique and systematic random sampling were utilized as sampling techniques and a total of 30 nurse educators and 30 student nurses were selected. The tools developed for the data collection were structured opinionnaire I to assess the opinion with regard to development of direct entry graduate program in midwifery, structured rating scale to determine the content of the syllabus, structured checklist to determine the practical competencies to be included in the direct entry graduate program in midwifery and structured opinionnaire II to determine the acceptability of the syllabus Tool was administered and based on the opinionnaire, rating scale and checklist, a syllabus for a 4 year direct entry graduate program in midwifery was developed. The syllabus was disseminated and after a week its acceptability was sought. Data gathered was analyzed and interpreted using descriptive and inferential statistics. Major findings of the study are as follows: Majority of the sample i.e. 60% of the nurse educators and 76.67 % of the student nurses had more than 75% agreement for the development of the direct entry graduate program in midwifery. The theoretical aspects of the syllabus were determined by the distribution of different subjects in the three year course. All the subjects included in the tool were given due importance however, it was suggested by majority of the sample to expand the course to 4 years as it was a graduate program. The practical aspects of the syllabus distributed under the heads viz. basic procedures, advanced procedures without assistance and advanced procedures with assistance were also given due importance. Thus all the subjects as well as practical components were included while developing syllabus. According to the opinion of nurse educators and student nurses, syllabus was found to be highly acceptable. Maximum subjects expressed that the criteria for the syllabus are fully met. The need for a direct entry graduate program in midwifery was felt as a need by both the nurse educators and student nurses and the syllabus developed for the same was found to be highly acceptable.